Sleep Pattern, Lifestyle Pattern, and Risks of Overall and 20 Types of Cancers: Findings From the UK Biobank Cohort - Yue-Ze Zhao; Yue-Ze Zhao; Wen-Li Zhang; Kai-Wen Zhang; Yong-Qiao He; Wen-Qiong Xue; Da-Wei Yang; Da-Wei Yang; Hua Diao; Hua Diao; Ruo-Wen Xiao; Ying Liao; et al. (International Journal of Public Health)
ObjectivesSleep health and other lifestyle behaviours are gaining increasing attention in public health, particularly for cancer prevention, but a comprehensive assessment is lacking.MethodsThe study included 380,042 UK Biobank participants. A healthy sleep score was constructed based on five sleep factors: chronotype, sleep duration, insomnia, snoring, and daytime dozing. A healthy lifestyle score was constructed based on four lifestyle factors: smoking, alcohol consumption, diet and physical activity. The effect of healthy sleep and lifestyle on cancer risk was examined by Cox proportional hazard models.ResultsBoth healthy sleep and lifestyle patterns were significantly associated with a reduced risk of overall cancer and specific cancer sites. Participants with healthy sleep and lifestyle patterns had a lower risk of overall cancer (HR = 0.72, 95% CI = 0.68–0.77), liver cancer (HR = 0.53, 95% CI = 0.31–0.90), bladder cancer (HR = 0.61, 95% CI = 0.47–0.79), lung cancer (HR = 0.22, 95% CI = 0.19–0.27), and colorectal cancer (HR = 0.80, 95% CI = 0.66–0.96) compared to those with unhealthy patterns.ConclusionOur findings highlight the importance of public health education and interventions to improve sleep and other lifestyle behaviours for cancer prevention.